Interface engineering to regulate oxidation dynamics of supported nanoparticles - Shiyuan Chen; Kai Zhang; Yuhui Chen; Bo Shao; Chaobin Zeng; Wentao Yuan; Hangsheng Yang; Zhong-Kang Han; Ying Jiang; Ze Zhang; Yong Wang (Nature Communications)
Abstract Understanding the oxidation of metal nanoparticles is crucial for various applications, particularly in heterogeneous catalysis, such as catalytic oxidation reactions, where metal nanoparticles are typically dispersed on supports. However, the dynamics of interaction between nanoparticles and oxygen, especially under the influence of supporting materials, remain poorly understood, significantly hindering the precise comprehension and regulation of nanoparticle oxidation dynamics. Here, we elucidate two distinct oxidation dynamics in supported nanoparticles using aberration-corrected environmental (scanning) transmission electron microscopy (E(S)TEM), i.e., preferential self-adaptive oxidation initiating at the nanoparticle-support interface, where the support facilitates oxidation, and surface oxidation, where the support inhibits oxidation. Our systematic calculations, corroborated by experimental validations, demonstrate that the interfacial epitaxial match plays a dominant role in determining the oxidation dynamics in oxygen. It serves as a key indicator for developing a straightforward interface engineering strategy to regulate both self-adaptive and surface oxidation processes. This work highlights the diversity of interface-determined oxidation behaviors and offers a strategy for regulating the oxidation dynamics of supported nanoparticles under identical conditions.